Discovery of a d-pro-lys peptidomimetic inhibitor of MMP9: Addressing the gelatinase selectivity beyond S1′ subsite. Issue 20 (15th October 2020) - Lenci, Elena; Contini, Alessandro; Trabocchi, Andrea
Graphical abstract: Abstract: Despite a high degree of structural similarity, it is known that MMP2 and MMP9 have distinct roles in the angiogenic switch and in cell migration, as they activate diverse signaling pathways. Indeed, inhibition of MMP2 and MMP9 can show beneficial or detrimental effects depending on the stage of tumor progression. Thus, the selective inhibition of gelatinases is of relevance for a successful drug lead, which has to be achieved despite the high structural similarity of the two gelatinases. Herein, the synthesis and evaluation of d -proline-derived hydroxamic acids containing amino appendages at C-4 as gelatinase inhibitors are reported. Inhibition assays enabled the identification of a > 200-fold selective MMP9 inhibitor when Lys was considered as a C-4 substituent, thus addressing gelatinase selectivity beyond the S1′ subsite, which is a major driver for selectivity. Molecular docking studies revealed the basic moiety of Lys as detrimental for inhibition of MMP2 as compared to MMP9.